Potential of Waste as Raw Silk Worm Biodegradable Surfactant - Ery Fatarina P; Mega Kasmiyatun; MF. Sri Mulyaningsih; T. Da Silva (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
Silkworm pupa is byproducts of silkworm farms are not fully utilized. This study aims to assess the potential silkworm waste as a raw material surfactant